Influence of gas sweep on methane recovery from hydrate-bearing sediments. (29th September 2015) - Wang, Xiao-Hui; Sun, Chang-Yu; Chen, Guang-Jin; He, Ya-Nan; Sun, Yi-Fei; Wang, Yun-Fei; Li, Nan; Zhang, Xiao-Xin; Liu, Bei; Yang, Lan-Ying
Abstract: Gas sweep is favorable for reducing the partial pressure of methane in free gas during the production of methane from hydrate-bearing sediments. To evaluate the influence of gas sweep on methane recovery, pure N2 was injected into hydrate-bearing sediments using a scale-up three-dimensional apparatus. The influences of injection mode, hydrate saturation, and N2 injection rate were investigated. The experimental results suggest that the methane recovery rate by pure N2 sweep is much quicker than direct depressurization. The driving force for hydrate dissociation increases with the increase of the N2 mole fraction, which further promotes the decomposition of hydrates and guarantees a high gas production rate. In terms of N2 injection rate on gas production, the higher the gas production, the more N2 that is required, which means the increase of gas production rate is at the cost of injecting much more N2 . Compared with the continuous mode, the batch injection mode is more suitable for controlling the hydrate dissociation rate and may be the lower risk way for hydrate exploitation. The gas sweep method may supply a new strategy that would be helpful to make low saturation hydrate reservoirs become a technically recoverable resource. Highlights: Gas sweep is in favor for reducing the partial pressure of methane in free gas. Methane recovery rate by N2 injection is much quicker than direct depressurization. The batch N2 injection mode is more suitable for controlling hydrate dissociation rate. The method of N2 sweep is quite suitable for low saturation hydrate reservoir.